COOPERATIVE PRINCIPLE IN THE FILM ‘CATCH ME IF YOU CAN’ - Putra, Agus Naryagali; Sudipa, I Nengah; Dewi, A.A.Sg. Shanti Sari (LITERA : Jurnal Bahasa Dan Sastra, 2024)
This study entitled Cooperative Principles Found in the film ‘Catch Me If You Can’ is aimed at describing the types of cooperative principles mostly used in the film. In analyzing the data, a qualitative method was applied using the cooperative principles theory proposed by Grice (1978) and the context of the situation by Halliday (1979) as supporting theories. The result of the study, film ‘Catch me if you can’ use a cooperative principle to the fullest, it surpass the potential observing the situation can give proper reason why the maxim flouted or applied by certain character in the film.